Primary stability of a new TendoClip fixation for tuberosity refixation in total shoulder arthroplasty - Uhler, Maximilian; Patzer, Thilo; Fleischer, Jörg; Knopp, Daniel; Knappe, Kevin; Bülhoff, Matthias; Kretzer, Jan Philippe (Journal of orthopaedic research, 2026)
Sufficient refixation and healing is crucial for the function of a reverse shoulder arthroplasty within the treatment of proximal humeral fractures. Conventional refixation with suture cerclage is time-consuming and leads to healing in only 60-70% of cases. This study used a biomechanical test to investigate two different refixation procedures for treating 4-fragment fractures of the proximal humerus. Eight paired humerus specimens were randomly assigned to two groups and treated with reverse shoulder prostheses. One group received conventional suture cerclage fixation for 4-fragment fractures, while the other used a novel TendoClip system with screw fixation. Both groups were subjected to increasing cyclic tensile forces until failure. Fragment movement relative to the prosthesis stem was measured to assess primary stability. Tensile forces generated in the first four load levels resulted in significantly different relative motions between the TendoClip and cerclage groups. 3 out of 8 specimens in the TendoClip group could be loaded over all load levels. This was not possible for any cerclage group specimens. Recorded failure mechanisms showed that fixed bone fragments of the cerclage procedure were affected significantly more often by loosening and visible relative movements compared to the TendoClip procedure. However, limitations of the TendoClip restoration were also observed. In 2 of 8 cases, a bone fragment was torn out of the fixation, and two other implants showed a loss of fixation in relation to the humerus. This study reveals that the TendoClip procedure could be an alternative to conventional cerclage fixation procedures in multifragmentary proximal humerus fractures.